Ketentuan Sanksi Menurut Hukum Persaingan Usaha Indonesia Ditelaah Dari Aspek Law is a Tool of Social Engineering - apriani, desi; Idris, Zulherman; Nasir, M (UIR Press, 2025)
After the job creation law, the provisions for sanctions for violations of the law on the prohibition of monopolistic practices and unfair business competition have changed significantly. Criminal sanctions are abolished, and administrative fines are changed to a maximum of 50 percent of net profits or 10 percent of total sales during the period of the violation. This change has attracted the attention of researchers who study from various aspects, including from the accounting aspect. In law, there is one of the famous theories, namely Law is a Tool of Social Engineering, which means that law is a tool for social engineering (changing society for the better). Based on that, the author sees that this study is important to be carried out so that the researcher will produce ideal conclusions and recommendations for future business competition law reform. This research is a normative legal research with a legislative, and theoretical approach. The results of the study show that sanctions according to the business competition law after the job creation law do not support the functioning of the business competition law to achieve positive changes among business actors according to the purpose of the law to prevent the occurrence of monopoly practices and unfair business competition. The author suggests that the provisions of the sanctions be reviewed and reviewed in the future reform of the business competition law so that the business competition law is able to form behavior and culture that prioritizes healthy business competition by prioritizing creation and innovation.